1985
DOI: 10.1073/pnas.82.19.6642
|View full text |Cite
|
Sign up to set email alerts
|

Phorbol ester induces a differential effect on the effector function of human allospecific cytotoxic T lymphocyte and natural killer clones.

Abstract: Six-day allosensitized human peripheral blood lymphocytes treated for 12-18 hr with phorbol 12-myristate 13-acetate (PMA) were found to lose the capacity to kill the specific target in a standard cell-mediated lympholysis (CML) assay, but they were still effective in their ability to kill the tumor cell line K562. We investigated which antigens on the cell membrane involved in alloimmune recognition might be modified by PMA, since it was found that in a lectin-dependent CML assay, the lytic mechanism was not i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

1986
1986
2007
2007

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…The amount of complex expressed on the surface of a developing T cell is often used as a gauge of maturity, with cells expressing high levels considered mature, and those expressing little or no CD3 considered immature. The transient decrease in CD3 expression observed in the present study is consistent with published reports of CD3 expression on activated human T cells (4,(6)(7)(8). This observation means that low level expression of CD3 may indicate an activated cell and not necessarily an immature one.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The amount of complex expressed on the surface of a developing T cell is often used as a gauge of maturity, with cells expressing high levels considered mature, and those expressing little or no CD3 considered immature. The transient decrease in CD3 expression observed in the present study is consistent with published reports of CD3 expression on activated human T cells (4,(6)(7)(8). This observation means that low level expression of CD3 may indicate an activated cell and not necessarily an immature one.…”
Section: Discussionsupporting
confidence: 93%
“…double positive state on activation (2), but in a recent study this was found not to occur (3). Several recent publications have suggested that CD3, CD4 and CD8 may be lost from the cell surface of human T cells upon activation in vitro (4)(5)(6)(7)(8)(9). Since T cells have been reported to be capable of returning to the thymus from the secondary lymphoid organs (10), this raises questions about the source of the minor subpopulations of double negative cells in the thymus (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…PB-NK cell purity was shown to be Ͼ90%. The selection of in vitro allogeneic-MHC-I-restricted effector T lymphocytes was performed as previously reported (31). Briefly, PBMC were cocultured for 6 days with irradiated EBV-transformed B cells in RPMI 1640 medium supplemented with penicillin (100 IU/ml), streptomycin (100 g/ml), L-glutamine (2 mM), and 10% heat-inactivated human serum (Jacques Boy Institute, Lyon, France).…”
Section: Cellsmentioning
confidence: 99%
“…After a 6-day culture the primed cells were restimulated for an additional 6 days with the specific stimulating cells in the presence of 10% human serum (HS)/RPMI containing 10% IL 2-conditioned medium [16]. The primed cells were then cloned by micromanipulation.…”
Section: Primed Culturesmentioning
confidence: 99%